The Neuroscience of the Flow State: Involvement of the Locus Coeruleus Norepinephrine System - van der Linden, Dimitri; Tops, Mattie; Bakker, Arnold B. (Frontiers in Psychology, 2021)
Flow is a state of full task engagement that is accompanied with low-levels of self-referential thinking. Flow is considered highly relevant for human performance and well-being and has, therefore, being studied extensively. Yet, the neurocognitive processes of flow remain largely unclear. In the present mini-review we focus on how the brain’s locus coeruleus-norepinephrine (LC-NE) system may be involved in a range of behavioral and subjective manifestations of flow. The LC-NE system regulates decisions regarding task engagement versus disengagement. This is done via different modes of baseline and stimulus-evoked norepinephrine release. We emphasize the theoretical and empirical overlap between the LC-NE system and flow. For both, a match between a person’s skill and task challenge is important in order to induce high levels task-related attention. Moreover, psychophysiological indicators of LC-NE system activity, such as eye pupil diameter and arousal are also sensitive to flow states. Flow is related to arousal in an inverted U-shape. Similarly, in theories on the LC-NE system, task engagement is highest with intermediate levels of arousal. We argue that knowledge about the role of the LC-NE system in establishing the flow experience may help to gain fundamental knowledge of flow and can contribute to unifying various empirical findings on this topic.